2003
DOI: 10.4028/www.scientific.net/kem.240-242.501
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ti-Substituted Hydroxyapatite

Abstract: A titanium-substituted hydroxyapatite has been prepared using titanium (IV) isopropoxide as a titanium source to obtain a biomaterial having an improved biocompatibility. From the XRD analysis, it was confirmed that the single-phase hydroxyapatite containing titanium has formed without revealing the presence of extra phases related to titanium dioxide or other calcium phosphate species. Titanium content was up to 0.73% by weight. EDS investigation confirmed the presence of titanium in the framework of hydroxya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…This is different from the situation with SiHA, where the radius of Si 4+ (0.40 Å) is close to that of P 5+ ; here, the substitution of SiO 4 for PO 4 is favorable. However, the increase in both the a and c axes of the TiHA unit cells does not totally support the Ti for Ca substitution, because a decrease in the unit cell parameter was expected as the radius of Ti is less than that of Ca, as found from the study by Hu et al [22] ( Table 3). The position of the metal ions in HA is an interesting subject.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This is different from the situation with SiHA, where the radius of Si 4+ (0.40 Å) is close to that of P 5+ ; here, the substitution of SiO 4 for PO 4 is favorable. However, the increase in both the a and c axes of the TiHA unit cells does not totally support the Ti for Ca substitution, because a decrease in the unit cell parameter was expected as the radius of Ti is less than that of Ca, as found from the study by Hu et al [22] ( Table 3). The position of the metal ions in HA is an interesting subject.…”
Section: Discussionmentioning
confidence: 80%
“…Using these methods, HA can be modified by Ti ions, such as Ti(SO 4 ) 2 . The preparation of titanium-containing HA using titanium isopropoxide has been reported previously by Kim et al [22]. They reported that a singlephase TiHA can be made with a titanium content of up to 0.73 wt.%, though it decomposed to tricalcium phosphate at high temperature.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Si, Mg 이온의 첨가에 관계없 이 제조된 공침 분말은 저결정성 HAp의 회절 패턴을 나타내었다. 이는 본 연구에서 공침분말의 Ca/P 몰비율 이 1.602로 1.67보다 적었지만 공침법에 의한 HAp 분 말 합성의 경우에 Ca/P 몰비율이 1.67보다 적어도 공침 분말은 HAp 회절 패턴을 나타낸다는 앞선 연구결과와 일치한다 [21]. 또한, 각각의 공침 분말의 X-선 회절패턴 에서는 첨가된 이온의 피크는 나타나지 않았다.…”
Section: 결과 및 고찰unclassified
“…Ion-incorporated hydroxyapatite can be used for a potential biological material in the form of porous body, granule and coating material on metal alloy substrates to improve biocompatibility [3][4][5][6]. Especially, incorporation of silicon into hydroxyapatite structure is of great interest since they play an important role in developing artificial bone [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%